121k views
1 vote
Transform the given quadratic function into vertex form f(x) = quadratic function into vertex form f(x) = quadratic function into vertex form
f(x) = (x-h)^(2) + k by completing the square.
a(x-h)^(2) +k by completing the square.


f(x) = 5x^(2) + 6x +4

1 Answer

4 votes

In the equation 5x^2 +6x +4

a = 5, b = 6 and c = 4

For the vertex form we need to find h:

h = b/2 over a = 6/2 over 5 = 3/5

Now find k:

k = 6 - b^2/4a = 4 - 6^2 / 4(5) = 11/5

Replace h in k in the vertex form formula to get:

5(x +3/5)^2 + 11/5

User Irakli Gabisonia
by
5.0k points